Is co2 laser Hemorrhoidectomy superior to conventional open Hemorrhoidectomy? - Sultan, Sa`ad H; Kamal, Zuhair B; Al-Atroshi, Mohammad A; Al-Fayadh, Raysan; Hussein, Wisam A (AL-Kindy College Medical Journal, 2010)
Background: Hemorrhoids are one of the mostcommon surgical conditions .Conventionalhaemorrhoidectomy was the traditional operation forthe treatment of hemorrhoids. Other modalities oftreatment had been used as an alternative operationsincluding CO2 laser haemorrhoidectomy.Objectives: To determine the outcome of treatmentof hemorrhoids by using CO2 laserhaemorrhoidectomy and its advantages overconventional surgeryMethods: This is a retrospective comparativeinterventional study of 1024 case of third degreehaemorhoids selected out of 1300 case ofhemorrhoids of different degrees, admitted toALKINDY, ALYERMOUK teaching hospitals andABD ALMAGEED private hospital, from May 1998to July 2002,they were treated by CO2 laserhaemorrhoidectomy and conventional surgery. Theyare divided into 2 groups randomly, 512 cases treatedby CO2 laser (group A), 512 cases treated byconventional surgery (group B). Both groups werestudied regarding operative time, hospital stay,healing time, post operative complications and costeffectiveness.Results: In GROUP A, the operative time rangedfrom 10 to 20 minutes with an average of 13 minutes.The hospital stay ranged from 4 to 12 hours with amean time of 10 hours as all cases were treated asday cases. Post operative pain was minimal in 50% ofpatients and required simple analgesia for treatmentwhile 50% had no pain. Bleeding occurred in lessthan 1% of cases, anal stenosis 3.3%, Infectionrecorded in 0.58% of patients.In GROUP B, Theoperative time ranged from 15 to 25 minutes with anaverage time of (19) minutes, hospital stay rangedfrom 24 to 48 hours with a mean time of 28 hours.Post operative pain recorded in all the patients(100%) and required narcotic analgesia for treatment,25 patients (4.8%) had varying degrees of bleeding,40 patients (7.8%) had infection, 25 patients (4.8%)had anal stenosis.In group A due to shorter hospitalstay, earlier healing of wounds, earlier return to workwhich was within 7 to 10 days, the surgical treatmentproved to be cost effective